Effect of respiratory muscle strengthening withbreathing exercises on ventilatory functions, aerobic fitness and their association with performance in elite rowers - Perera, D. P.; Ariyasinghe, A.; Kariyawasam, A. (BMC Research Notes, 2020)
Rowing is one of the most physically demanding endurance sports requiring high levels of ventilation. The aim of this study was to investigate the effect of RMT on ventilatory parameters, aerobic fitness and rowing ergometer performance among 20 professional rowers (experimental (n=11) and control (n=9) aged 20-35 years in Sri Lanka.